Efeito antiparasitário do curcuminoide sintético (1E,4E)-1,5-BIS(4-metoxifenil) penta-1,4-dien-3-ona sobre Trypanosoma cruzi cepa Y: mecanismos de ação e sinergismo - Cavalcante, John Washington (2024)
Chagas Disease (CD), transmitted by T. cruzi, is considered a neglected disease and is still a major public health problem. The main drug available for treatment is benznidazole, which has serious adverse reactions and little efficacy in the chronic phase of CD. Therefore, this study was designed to investigate the potential therapeutic effect of the synthetic curcuminoid derivative (1E,4E)-1,5-bis(4-methoxyphenyl) penta-1,4-dien-3-one (DBAn) against T. cruzi strain Y using in vitro and in silico models. Initially, a cytotoxicity test was carried out in which the treatment of LLC-MK2 cells with DBAn showed a CC50 of 1277 + 348, as well as a selectivity index of 36, demonstrating a value 15 times higher than benznidazole. In addition, the curcuminoid derivative showed inhibitory activity in all three life stages of T. cruzi. In epimastigote forms, DBAn showed an IC50 of 61.81 + 0.83 μM, with significant values between concentrations 62.5 - 1000 μM. At these same concentrations, DBAn showed an LC50 of 35.46 + 0.23 μM in trypomastigote forms. In the intracellular and replicative forms of T. cruzi, DBAn was able to decrease the number of infected cells as well as the number of amastigotes at all the concentrations tested: 15.6, 31.2 and 62.5 μM. In flow cytometry assays, DBAn was able to induce the production of ROS (DCFH2-DA); as well as changes in mitochondrial membrane potential (Rho123 - ΔΨm); cell death inducing pathways were also analyzed, such as necrosis (7-AAD) and apoptosis (Ax/PE), where the curcuminoid derivative induced significant cell death events in the parasites. The in silico study allowed us to predict that DBAn is a liposoluble molecule with good oral bioavailability. In molecular docking, our results showed interactions between DBAn and the key enzymes of T. cruzi (GAPDH, Trypanothione Reductase, Cruzaine).An increase in affinity energy values (ΔG) was observed compared to Bz. Synergism tests between DBAn and Bz showed no cytotoxicity in LLC-MK2 cells. The combined effect of DBAn and Bz caused a notable reduction in cell viability in epimastigote and trypomastigote forms at doses > 10 μM. In summary, this study has shown respectable characteristics of DBAn against the Y strain of T. cruzi, which can be developed into a leading molecule for the treatment of Chagas disease.